1998
DOI: 10.1046/j.1365-313x.1998.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bHLH and MYB domain proteins: species‐specific regulatory differences are caused by divergent evolution of target anthocyanin genes

Abstract: The regulatory anthocyanin loci, an1, an2, an4 and an11 of Petunia hybrida, and r and c1 from Zea mays, control transcription of different sets of target genes. Both an2 and c1 encode a MYB-type protein. This study reports the isolation of a P. hybrida gene, jaf13, encoding a basic helix-loop-helix protein that, on the basis of sequence homology and intron/exon structure, represents the P. hybrida orthologue of the Z. mays r genes. Ectopic expression of an2 and jaf13 is sufficient for activation of the dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
312
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(325 citation statements)
references
References 46 publications
12
312
0
1
Order By: Relevance
“…the responsiveness of AtF3H but not AtDFR to MYB12 in contrast to the responsiveness of ZmDFR but not ZmF3H to ZmP, probably reflects the divergent evolution of the promoter sequences of these two genes, constituting the basis for the observed metabolic difference between maize and Arabidopsis. A similar differential regulation has also been described for the CHS promoter between maize and P. hybrida (Quattrocchio et al, 1998).…”
Section: Myb12 and Zmp Share Fundamental Functional Characteristicssupporting
confidence: 73%
“…the responsiveness of AtF3H but not AtDFR to MYB12 in contrast to the responsiveness of ZmDFR but not ZmF3H to ZmP, probably reflects the divergent evolution of the promoter sequences of these two genes, constituting the basis for the observed metabolic difference between maize and Arabidopsis. A similar differential regulation has also been described for the CHS promoter between maize and P. hybrida (Quattrocchio et al, 1998).…”
Section: Myb12 and Zmp Share Fundamental Functional Characteristicssupporting
confidence: 73%
“…Previous experiments showed that the introduction of a 35S-an2 gene in the an4 Ϫ line W115 and the hybrid W115/ W59 restored pigmentation in the corolla (complementation of an2) as well as the anthers, indicating that ectopically expressed AN2 complements an4 (Quattrocchio et al, 1998). Figure 7 shows that an4 Ϫ anthers of W115/W59 contain very small amounts of dfr and an1 mRNA (lanes 13 to 15).…”
Section: Regulation Of An1 Expression By An2 and An4mentioning
confidence: 79%
“…In addition, transient assays on immature maize kernels demonstrate that TT2 can substitute efficiently for C1 when used in combination with B-Peru (P. Perez, personal communication), thus indicating that C1 and TT2 activate the same target genes in the maize anthocyanin pathway. Strikingly, TT2 displays a lower amino acid conservation with the petunia AN2 MYB factor, although these two proteins appear to regulate similar sets of flavonoid structural genes in their respective hosts (Quattrocchio et al, 1993(Quattrocchio et al, , 1998(Quattrocchio et al, , 1999. …”
mentioning
confidence: 99%